Peran Penyuluh Pertanian Dalam Pengembangan Kelompok Tani Di Desa Sukarame Kecamatan Kota Agung Kabupaten Lahat - Hartini, Indra (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to determine the role of agricultural extension workers in the development of farmer groups in Sukarame Village, Kota Agung District, Lahat Regency. The selection of research locations was carried out intentionally (purposive sampling). Respondents in this study came from the chairman, secretary, and three members of the farmer groups. The farmer groups that became the research sample were 10 farmer groups with 5 farmer groups being advanced classes and 5 farmer groups being beginner classes. Data analysis used in this study were validity tests, Likert scales, and correlation tests. The results of this study indicate that the level of role of Agricultural Extension Workers in the development of Farmer Groups in Sukarame Village, Kota Agung District, Lahat Regency is classified as high with a value of 75.136%. The percentage of the role of extension workers as Facilitators is 74.88%, Innovators 74.40%, Motivators 74.24%, Dynamicators 75.36%, and Educators 74.08%. This indicates that Agricultural Extension Workers in Sukarame Village, Kota Agung District, play a good role and produce a percentage in the High category. The results of the correlation test of the Role of Extension Workers (X) in the Development of Farmer Groups (Y) produce a sufficient, strong, and significant relationship.